PENGARUH JUMLAH BIBIT PADA LUBANG TANAM DAN FREKUENSI PENGENDALIAN GULMA TERHADAP PERTUMBUHAN DAN PRODUKSI PADI SAWAH (Oriza sativa L.) DENGAN METODE SRI - Trisno Hutasoit; Husna Yetti; Arnis En Yulia (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The rice plant (Oryza sativa L.) is a kind of plant that produce rice which is the become main food for majority of Indonesian people. The total of people that rise increasingly must balance with the increasing of  rice production. One of the methods to get the increasing of rice production is applying the System of Rice Intensification (SRI). This research aims to determine the intraction of seeds number and weeds  frequency control on the growth and production of lowland rice. The experiment sites in lowland field of Balai Benih Induk Holtikultura, Kaharudin Nasution Street, Padang Marpoyan, Pekanbaru City, Riau Province. Started on March Until July 2012. Research using Randomized Block Design (RBD) factorial, the first factor consists of 4 threatments (1 seed/hole,2 seeds/hole, 3 seeds/hole, 4 seeds/hole) and the second factor consists of 3 threatments  twice weeding (20, 40 days after planted), three times weeding (20, 30, 40 days after planted) and four times weeding ( 10, 20, 30, 40 days after planted) by  3 repetitions. Data was analyzed by analysis of variance and further test by Duncan’s Multiple Range Test (DNMRT) at the level of 5%. The research showed that the intraction seeds number and weeds  frequency control were significant to all parameters except in parameter of 1000 seeds weight. The threatment 4 seeds/hole and four times weeding 10, 20, 30, 40 days after planted gave the best effect on growth and production of lowland rice.   Keyword: lowland rice, seeds number, weeds frequency control, SRI.